Novel isothermal calorimetry approach to monitor micronutrients stability in powder forms. (January 2020) - Morozova, Ksenia; Bulbarello, Andrea; Schaefer, Christian; Funda, Elger; Porta, Fabiola; Scampicchio, Matteo
Abstract: Oxidative stability is critical in guaranteeing the declared shelf life of new formulations and contributes significantly to time-to-market efficiencies. In this study an innovative method based on isothermal calorimetry is proposed for monitoring the stability of vitamin A acetate formulations with one or more antioxidants, such as butylated hydroxytoluene, ethoxyquin, tocopherol and rosemary extract. The results were correlated with conventional stability tests utilizing liquid chromatography (LC). The efficiency of three drying technologies (spray drying, spray granulation, and beadlet) were compared. The initial heat flow values obtained from isothermal calorimetry experiments were used to identify the most efficient drying technology, antioxidant system, that is beadlet. The resulting rate constants of vitamin degradation calculated from the LC data were positively correlated with the initial heat flow values. This study demonstrated that the performance of isothermal calorimetry was far superior when compared with traditional methods. In addition, this methodology allowed the detection of micronutrient stability in complex powder mixtures in only a few hours without the need for sample preparation. This approach could therefore potentially be applied to industry and academic environments for the prediction of micronutrients stability. Graphical abstract: Image 1 Highlights: Novel method for control of stability of encapsulated micronutrients. Efficiency of three different drying technologies was compared. Comparison of vitamin A formulations with various antioxidants. Correlation with conventional stability tests by liquid chromatography.